“Thief” shoots on rootstocks grafted with net melons - Ito, L. A. [UNESP]; Gaion, L. A. [UNESP]; Galatti, F. S. [UNESP]; Braz, L. T. [UNESP] (International Society for Horticultural Science (ISHS), 2019)
Cleft grafting in cucurbits is the removal of the apical meristem, leaving only the cotyledons between which the graft will be placed. With the removal of the apical meristem, the dormancy of lateral buds in the axil of the cotyledons is broken, causing the growth of “thief” shoots. These shoots should be removed for the graft to grow vigorously. However, the procedure shoot removal causes an increase in manpower, resulting in higher production cost of the plant. This study aimed to assess the “thief” shoots rate of 17 rootstocks (Cucurbitaceae), grafted with two cultivars of net melon (‘Bonus no 2’ and ‘Fantasy’). The cleft graftings were performed 14 days after sowing and kept in a moist chamber. Evaluations of rootstocks sprouting were performed at 10 days after grafting. A randomized blocks design was used with 17 treatments and five replicates in two cropping seasons: autumn-winter and spring-summer. The rootstocks, ‘Hybrid Keij F1’ and ‘Korean Progeny’ presented the highest rates of “thief” shoots, increasing the costs on manpower used for their removal. Rootstocks: melon ‘Redondo Gaúcho’ and melon ‘Redondo Amarelo’ presented the lowest rates of “thief” shoots, therefore being the most suitable as rootstocks for net melon, reducing production costs of these plants.
Keywords: Cucumis melon; Grafting; Rootstocks